Synthesis, Evaluation and Structure-Activity Relationships of 5-Alkyl-2,3-dihydroimidazo[1,2-c]quinazoline, 2,3-Dihydroimidazo[1,2-c]quinazolin-5(6H)-thiones and their Oxo-analogues as New Potential Bronchodilators - Bahekar, Rajesh H.; Ram Rao, A. Raghu (Arzneimittelforschung, 2001)
With an aim to obtain potent bronchodilators, two series of 5-alkyl-2,3-dihy-droimidazo[1,2-c]quinazolines (Va-l), 2,3-dihydroimidazo[1,2-c]quinazolin-5-(6H)-thiones (VIIIa-d) and their oxo-ana-logues (IXa-d) have been designed. The compounds Va-l were synthesized by two alternative routes. The former (Method A) based on the dehydrocyclization of 4-(1-hydroxyethyl)-aminoquinazoline (IV) and the latter (Method B) involves the usage of 2-aminobenzonitrile (VI) which on reaction with ethylenediamine leads to the formation of the key intermediate 2-(2-aminophenyl)-4,5-dihydro-1H-imidaz-oles (VII). Finally the intermediate VII on condensation with different acidanhyd-rides yielded the title compound V. In general method-A resulted the compound V in quantatively higher yields. 2,3-Dihydroimidazo[1,2-c]quinazolin-5 (6H)-thiones (VIII) were obtained by condensing VII with carbon disulfide and a further oxidation of VIII gave their corresponding oxo-analogues (IX). The title compounds V, VIII and IX were evaluated for their bronchodilator activity using in vitro and in vivo (standard animal models) methods. All the test compounds exhibited bronchodilatory activity. The structure activity relationship studies indicated good correlation between the nature of the substituent and bronchodilatory activity. In the 5-alkyl substituted compounds V, a longer alkyl chain showed higher bronchodilatory activity. Compounds VIII and IX were found to be less potent and replacement of sulphur with oxygen showed no significant effect on the biological activity. The presence of halogens altered the biological activity in both the series. Among the compounds tested, 9-iodo-5-(n-pro-pyl)-2,3-dihydroimidazo[1,2-c]quinazo-line (Vl) was found to be the most potent (percentage protection = 87.1 %; relative activity = 1.1 compared to the standard aminophylline).
Keywords: Asthma; Bronchodilators; Imidazo[1,2-c]quinazolines; Imidazo[1,2-c]quinazolinones; Imidazo[1,2-c]quinazolinthiones